Biliary ascariasis, diagnosis by cholangioresonance - Pouy, Andrés; Haro, Camila; Almada, Mario (Cirugía del Uruguay, 2020)
Ascaris lumbricoides corresponds to the most frequent helminthiasis of the digestive tract, the highest prevalence is seen in countries with tropical and underdeveloped climates. Adult parasites, in addition to the digestive tract, can invade the pancreatic bile ducts.